Ross syndrome: a case series of five patients - Sharmeen, Ayesha; Mehdi, Husaini S. Haider; Adil, Mohammad; Rehman, Suhailur (International Journal of Research in Dermatology, 2026)
Ross syndrome, a rare neurological disorder, is characterized by the combination of three primary features: segmental anhidrosis, tonic pupils, and areflexia. The exact aetiology remains unclear, but it involves dysfunction in the autonomic nervous system, specifically affecting the sympathetic pathways. Patients often experience reduced sweating, particularly in specific body regions, alongside pupillary abnormalities and diminished reflex responses. Due to its rarity, further research is needed to understand its pathophysiology, optimize treatment strategies, and improve patient outcomes. In our case series of five patients, a diagnosis of ’complete’ Ross syndrome was made for two patients, while the remaining patients were diagnosed with ’incomplete’ Ross syndrome. The rarity of Ross syndrome underscores the importance of detailed clinical reporting, as it may lead to improved patient care and outcomes.